Resveratrol Exerts Anti-Osteoarthritic Effect by Inhibiting TLR4/NF-κB Signaling Pathway via the TLR4/Akt/FoxO1 Axis in IL-1β-Stimulated SW1353 Cells - Xu X; Liu X; Yang Y; He J; Jiang M; Huang Y; Liu X; Liu L; Gu H (Dove Medical Press, 2020)
Xiaolei Xu,1,2,* Xudan Liu,1,* Yingchun Yang,1 Jianyi He,1 Mengqi Jiang,1 Yue Huang,1 Xiaotong Liu,1 Li Liu,1 Hailun Gu3 1Department of Nutrition and Food Hygiene, School of Public Health, China Medical University, Shenyang, People’s Republic of China; 2Department of Nutrition and Food Hygiene, School of Public Health, Beihua University, Jilin, People’s Republic of China; 3Department of Orthopedics, Shengjing Hospital, China Medical University, Shenyang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hailun GuDepartment of Orthopedics, Shengjing Hospital, China Medical University, Shenyang 110004, Liaoning Province, People’s Republic of ChinaTel +86-18940257206Email guhailun_@163.comLi LiuDepartment of Nutrition and Food Hygiene, School of Public Health, China Medical University, Shenyang 110122, Liaoning Province, People’s Republic of ChinaTel +86-18900910766Email lliu@cmu.edu.cnPurpose: Osteoarthritis (OA) is associated with chronic low-grade inflammation. Resveratrol exerts protective effects on OA through its anti-inflammatory property; however, the mechanism of resveratrol on anti-inflammatory signaling pathways has not been fully elucidated yet. The aim of the present study was to investigate whether resveratrol-mediated PI3K/Akt expression is linked to TLR4/NF-κB pathway and the role of TLR4/Akt/FoxO1 axis in the anti-osteoarthritic effect of resveratrol.Methods: SW1353 cells stimulated by IL-1β (10 ng/mL) were cultured in the presence or absence of resveratrol (50 μM) and then treated with TLR4 siRNA, PI3K inhibitor LY294002 or FoxO1 siRNA, respectively. The associated proteins of TLR4 signaling pathways and TLR4/Akt/FoxO1 axis were evaluated by Western blot. The level of IL-6 in the supernatant was detected by ELISA.Results: IL-1β treatment increased the expression of TLR4/NF-κB and phosphorylation of PI3K/Akt and FoxO1, while additional resveratrol further upregulated the expression of PI3K/Akt and FoxO1 phosphorylation but downregulated TLR4 signals in SW1353 cells. Further analyses by the inhibition of TLR4, PI3K/Akt and FoxO1 signaling pathways, respectively, showed that the activation of TLR4 can induce PI3K/Akt phosphorylation, which increases the phosphorylation of FoxO1 and inactivates it. Next, inactivated-FoxO1 can reduce the expression of TLR4, which forms a self-limiting mechanism of inflammation. Resveratrol treatment can upregulate PI3K/Akt phosphorylation and inactivate FoxO1, thereby reducing TLR4 and inflammation.Conclusion: This study reveals that TLR4/Akt/FoxO1 inflammatory self-limiting mechanism may exist in IL-1β-stimulated SW1353 cells. This study reveals a novel cross-talk mechanism which is between integrated PI3K/Akt/FoxO1 signaling network and TLR4-driven innate responses in IL-1β-stimulated SW1353 cells. Resveratrol may exert anti-OA effect by enhancing the self-limiting mechanism of inflammation through TLR4/Akt/FoxO1 axis.Keywords: resveratrol, toll-like receptor 4, osteoarthritis, interleukin-1β, forkhead box O1, phosphoinositide-3-kinase/protein kinase B